Regulation of interest rates on bank deposits - Cox, Albert H. (Ann Arbor : Bureau of Business Research, Graduate School of Business Administration, University of Michigan, 1966)
The book examined the historical background of the regulation of interest rates on banks deposits and its implications for domestic economic policy.
Bibliography: p. 199-207.
usc 15/05/2017
Loans
Keywords: Interest rates